(untitled) (The University of Nairobi Journal of Language and Linguistics, 2023)
In this paper we explore the differences in the Agreement Phrase that have arisen in Western Nilotic languages, a sub-family of the Nilo-Saharan language family. We adopt a Principles and Parameters approach which makes the claim that languages are fundamentally similar at the deep structure. It places emphasis on morphological operations as being responsible for many of the differences among languages. Our study finds that there are now clear grammatical differences that have emerged among these related languages. We have found out that Northern Luo languages (N. Luo) are closer in their grammatical operations as compared to Southern Luo languages (S. Luo). This approach provides us with the theoretical devices that have enabled us to explain a number of puzzling grammatical phenomena in these languages.